[PP.20.06] THE INFLUENCE OF SLOW BREATHING TRAINING ON PHYSICAL EXERCISE CAPACITY AND SLEEP DISTURBANCES IN PATIENTS WITH CHRONIC HEART FAILURE. (September 2016) - Kielbasa, G.; Drozdz, T.; Debicka-Dabrowska, D.; Styczkiewicz, K.; Klocek, M.; Malfatto, G.; Bednarek, A.; Olszanecka, A.; Bilo, G.; Czarnecka, D.; Parati, G.; Kawecka-Jaszcz, K.
Abstract : Objective: Slow breathing has favorable acute effects in chronic heart failure (CHF) patients. Aim of this study was to test the feasibility and efficacy of a new nonpharmacological approach to CHF management based on slow breathing training (SBT). Design and method: The study was a cross-over open trial where patients, in random order, underwent a 10–12 week period of SBT with RESPeRATE device (InterCure Ltd., Lod, Israel) and a 10–12 week follow-up under usual care. Patients during SBT were asked to perform each day two separate 15-min sessions of device-guided SBT at a breathing frequency of 6 breaths per minute. In all patients, clinical data collection, echocardiography, polysomnography, 6 minute walking test (6MWT) and laboratory tests were performed at baseline and after each study phase. Results: 74 patients completed the study, with the following baseline characteristics: age 62.9 ± 11.9 years, 59 M/15F, 52 with ischemic CHF, NYHA Class I:7 Class II:51, Class III:16, left ventricular ejection fraction 30.4 ± 8.1 %, hypertension: 47, history of stroke: 5, diabetes: 28. Compared with values before SBT, after completion of the SBT phase we observed an increase in 6MWT distance (from 482.3 ± 118.9 to 499.2 ± 116.9 m; p = 0.008) and in left ventricular ejection fraction [from 30.0 (25.0–37.0) to 32.0 (27.0–37.0) %; p = 0.047], and a decrease in apnea-hypopnea index (from 9.9 ± 10.3 to 7.9 ± 8.4; p = 0.015). A trend towards reduction of pulmonary artery pressure [35 (27–45) vs 32 (25–40) mmHg; p = 0.063] was also seen. Conclusions: Our data indicate that SBT is feasible in CHF patients and that it is associated with an improvement in functional capacity, haemodynamic variables and sleep disordered breathing severity. These results support SBT as a novel and useful component of cardiorespiratory rehabilitation programs in CHF.